Arctic craftivism and revitalisation of crafting - Huhmarniemi, Maria (Invisibilidades 15: Arte como Escultura Social, 2021)
Knitting is a form of craft that is practised in many cultures with local features. Colour combinations, specific qualities of yarn, and decorative patterns give local character to mittens, cardigans, and other knits. In many regions, patterns have a communicative function: they carry cultural symbols and representations of cultural identities. In this visual essay, I describe artistic productions that have included participatory methods and the use of patterns as visual communication. The study follows the approach of art-based action research in which Northern cultural revitalisation is promoted. The artworks can be viewed as craftivism as the practice of engaging creativity regarding political or social causes.